In silico selection of Arabidopsis thaliana ecotypes with enhanced stress tolerance. - Prasch, Christian; Sonnewald, Uwe (Plant Signaling & Behavior, 2013)
Climate models predict increased occurrences of combined abiotic and biotic stress. Unfortunately, most studies on plant stress responses include single or double stress scenarios only. Recently, we established a multi-factorial system in Arabidopsis thaliana (Arabidopsis) to study the influence of simultaneously applied heat, drought, and virus. Our transcriptome analysis revealed that gene expression under multi-factorial stress is not predictable from single stress treatments. Combined heat and drought stress reduced expression of defense genes and genes involved in R-mediated disease responses, which correlated with increased susceptibility of Arabidopsis to virus infection. Eleven genes were found to be differentially regulated under all stress conditions. Assuming that regulated expression of these genes is important for plant fitness, Arabidopsis ecotypes were clustered according to their expression. Interestingly, ecotypes showing a close correlation to stressed Col-0 prior stress treatment showed improved growth under stress conditions. This result suggests a functional relevance of these genes in stress tolerance.